P283 The alberta 2016–2020 STBBI operational strategy and action plan: collective impact to address the provincial STI outbreak. (14th July 2019) - Egan, Cari; Wood, Christopher; Strong, David; Gratrix, Jennifer; Smyczek, Petra; Prasad, Abhaya; Rathjen, Lindsay
Abstract : Background: In April of 2016, a provincial sexually transmitted infections (STI) outbreak was declared in Alberta. In response to sharply rising rates, Alberta formed the Alberta Sexually Transmitted and Blood Borne Infection (STBBI) Network (ASN) and developed the 2016–2020 STBBI Operational Strategy and Action Plan (OSAP). The aim of the STBBI OSAP is to transform STBBI care in Alberta by leveraging engagement and commitment from within the ASN to achieve collective impact and develop wrap around shared care models through formalized interagency collaboration. Methods: ASN has grown to include over 500 stakeholders representing approximately 200 community-based, provincial and federal organizations including communities most affected by STBBI (Indigenous, LGBTQ2+, immigrants, and street involved clients). The OSAP comprises 74 recommendations that focus on five pillars of client-centred STBBI care: (1) prevention, (2) testing/screening, (3) treatment, (4) linkage to care, and (5) stigma. Seven working groups designed 15 project concepts with endorsement from the Steering Committee to optimize achievement of prioritized recommendations. Results: Implementation of STBBI OSAP priority recommendations is still underway in 2019. Some prioritized action items include: PrEP guidelines and training program for designated prescribers; a validation study of self-collected gonorrhea/chlamydia NAAT specimens to improve access to low barrier testing opportunities; expedited partner therapy; expanded Hepatitis C treatment access in Indigenous communities; education for primary care providers to increase access and linkage to STBBI care; and formalizing interagency collaboration through the development of STBBI wrap around shared care model demonstration projects. Conclusion: The STBBI OSAP is an innovative, comprehensive, and collaborative intersectoral approach to address the high burden of STBBI in Alberta and to strengthen the provincial outbreak response. The strength of this provincial initiative is the engagement and collaboration amongst ASN stakeholders to achieve long lasting impact and sustainability of both systemic and operational interventions. Disclosure: No significant relationships.